2014
DOI: 10.1007/s10972-014-9397-9
|View full text |Cite
|
Sign up to set email alerts
|

What Makes the Difference? Teachers Explore What Must be Taught and What Must be Learned in Order to Understand the Particulate Character of Matter

Abstract: The concept of matter, especially its particulate nature, is acknowledged as being one of the key concept areas in learning science. Within the framework of learning studies and variation theory, and with results from science education research as a starting point, six lower secondary school science teachers tried to enhance students' learning by exploring what must be learnt in order to understand the concept in specific way. It was found that variation theory was a useful guiding principle when teachers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
16
0
3
Order By: Relevance
“…Fourth, the selection of the subatomic structure of matter as the topic of the learning unit on which the professional development program was based is ideal for the purpose of our study. It not only represents a prominent and current topic of the physics curriculum for middle and high school but is also considered a fundamental topic in science (Vikström, ). Furthermore, education research has shown that middle and high school students have significant difficulties integrating the concept of particles into their conceptions of everyday life (Adbo & Taber, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the selection of the subatomic structure of matter as the topic of the learning unit on which the professional development program was based is ideal for the purpose of our study. It not only represents a prominent and current topic of the physics curriculum for middle and high school but is also considered a fundamental topic in science (Vikström, ). Furthermore, education research has shown that middle and high school students have significant difficulties integrating the concept of particles into their conceptions of everyday life (Adbo & Taber, ).…”
Section: Discussionmentioning
confidence: 99%
“…The data presented come from a larger study about mathematics and science teachers' teaching after they are engaged in a theory-driven lesson study intervention of 1.5 years, in which they used variation theory. One finding is that teachers, after participating in this particular professional development, make other aspects of the content noticeable for the students through their teaching Nilsson 2014;Vikstrom 2014). The aim of this paper is to demonstrate how a lesson design can be analyzed from the point of view of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…It is an "action research which aims to improve classroom teaching and learning by enhancing teacher professional development" (Keung, 2009;Vikström, 2014). In line with Marton and Lo (2007), it is a designed experiment aiming at making students as well as teachers" learning possible.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…School"s administration and community support are paramount vital in enhancing teachers collaborative working. When teachers are recognized, valued, respected, and encouraged to work jointly in facing common challenges prevailed in the schools, they are more likely to develop sophisticated understanding (Vikström, 2014), and sense of togetherness toward high purpose of improving students" learning. Capabilities to untangle some complex issues in schools such as complex discipline topics such as the LCA pedagogy, cannot be handled with an individual teacher, rather with school teachers, collaboratively.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%